Early spinal cord pseudoatrophy in interferon‐beta‐treated multiple sclerosis. (17th November 2022) - Matusche, Britta; Litvin, Ludmila; Schneider, Ruth; Bellenberg, Barbara; Mühlau, Mark; Pongratz, Viola; Berthele, Achim; Groppa, Sergiu; Muthuraman, Muthuraman; Zipp, Frauke; Paul, Friedemann; Wiendl, Heinz; et al.
Abstract: Background and purpose: Brain pseudoatrophy has been shown to play a pivotal role in the interpretation of brain atrophy measures during the first year of disease‐modifying therapy in multiple sclerosis. Whether pseudoatrophy also affects the spinal cord remains unclear. The aim of this study was to analyze the extent of pseudoatrophy in the upper spinal cord during the first 2 years after therapy initiation and compare this to the brain. Methods: A total of 129 patients from a prospective longitudinal multicentric national cohort study for whom magnetic resonance imaging scans at baseline, 12 months, and 24 months were available were selected for brain and spinal cord volume quantification. Annual percentage brain volume and cord area change were calculated using SIENA (Structural Image Evaluation of Normalized Atrophy) and NeuroQLab, respectively. Linear mixed model analyses were performed to compare patients on interferon‐beta therapy ( n = 84) and untreated patients ( n = 45). Results: Patients treated with interferon‐beta demonstrated accelerated annual percentage brain volume and cervical cord area change in the first year after treatment initiation, whereas atrophy rates stabilized to a similar and not significantly different level compared to untreated patients during the second year. Conclusions: These results suggest that pseudoatrophy occurs not only in the brain, but also in the spinal cord during the first year of interferon‐beta treatment.